An observational study of adolescent health outcomes associated with school‐based health service utilization: A causal analysis. (18th March 2019) - Denny, Simon; Grant, Sue; Galbreath, Ross; Utter, Jennifer; Fleming, Theresa; Clark, Terryann
Abstract : Objective: Our aim is to examine the unbiased association between use of school‐based health services (SBHS) and student health outcomes. Data Sources: Data are from a nationally representative health and well‐being survey of 8500 New Zealand high school students from 91 high schools. Study Design: Student data were linked to the level of SBHS available to them: no SBHS, regular clinics from visiting health professionals, a health professional onsite, or a health team onsite. Data Collection/Extraction Methods: Causal analyses are used to compare utilization of SBHS and their association with student‐reported health outcomes, including foregone health care, depressive symptoms, emotional and behavioral difficulties, suicide risk, substance use, and unsafe sexual behaviors. Principal Findings: Results from the multinomial propensity score–weighted regressions show that the use of SBHS was associated with poorer health outcomes, suggesting that selection bias was present due to unmeasured confounders. Instrumental variable analyses found that that students using team‐based SBHS had a 4.7 percent (95% CI 0.5‐8.9) probability of high levels of depressive symptoms compared to 14.2 percent (95% CI 11.5‐16.8) among students not using team SBHS. For suicide attempt, students using team‐based SBHS had a 2.0 percent (95% CI −0.3‐4.2) probability of a suicide attempt in the previous 12 months compared to 5.6 percent (95% CI 2.6‐8.5) among students not using team SBHS. Conclusions: These analyses suggest that team‐based SBHS are associated with better mental health among students who attend them.